2014
DOI: 10.1096/fj.14-250555
|View full text |Cite
|
Sign up to set email alerts
|

The human liver‐specific proteome defined by transcriptomics and antibody‐based profiling

Abstract: Human liver physiology and the genetic etiology of the liver diseases can potentially be elucidated through the identification of proteins with enriched expression in the liver. Here, we combined data from RNA sequencing (RNA-Seq) and antibody-based immunohistochemistry across all major human tissues to explore the human liver proteome with enriched expression, as well as the cell type-enriched expression in hepatocyte and bile duct cells. We identified in total 477 protein-coding genes with elevated expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…However, some of the 17β-HSD family members, including 17β-HSD-4, -7, -10, and -12, have been shown to participate in CHO and fatty acid metabolism, suggesting that 17β-HSD13 might also play a role in lipid metabolic pathways. A recent study reported that hepatic up-regulation of 17β-HSD13 was observed in patients with fatty liver, which is consistent with our findings and further supports a role of this enzyme in the pathogenesis of NAFLD (37).…”
Section: β-Hsd13 Promotes Lipogenesis In Mouse Livers and Culturedsupporting
confidence: 93%
“…However, some of the 17β-HSD family members, including 17β-HSD-4, -7, -10, and -12, have been shown to participate in CHO and fatty acid metabolism, suggesting that 17β-HSD13 might also play a role in lipid metabolic pathways. A recent study reported that hepatic up-regulation of 17β-HSD13 was observed in patients with fatty liver, which is consistent with our findings and further supports a role of this enzyme in the pathogenesis of NAFLD (37).…”
Section: β-Hsd13 Promotes Lipogenesis In Mouse Livers and Culturedsupporting
confidence: 93%
“…Remarkably, nearly one-third of glutathionylated proteins in our study were localized in the mitochondria, while mitochondrial proteins typically account for only 7% of the total liver proteome (28). The enrichment of mitochondrial proteins in our dataset agrees with the central role that mitochondrial dysfunction plays in APAP-induced hepatotoxicity (29).…”
Section: Apap-induced Protein Glutathionylation Is Dose and Bioactivasupporting
confidence: 82%
“…The tissues with the most mRNAs highly enriched (at least 5× the levels in all other tissues) are testis (999) and brain (318). Several tissue-specific HPA publications have been published, and more are expected during 2015 with tissue-specific immunohistochemical and transcript evidence to guide specimen selection for further MS studies, for example, describing the brain, 18 liver, 19 testis, 20 kidney, 21 pancreas, 22 skin, 23 adipose tissue, 24 gallbladder, 25 lung, 26 gastrointestinal tract, 27 and cardiac and skeletal muscle. 28 HPA, v14, will be released in Fall 2015 along with a novel Rodent Brain Atlas comprising immunofluorescently stained whole-mouse-brain sections.…”
Section: A New Phase For the Human Protein Atlasmentioning
confidence: 99%